Comparison of efficacy of 0.75% ropivacaine and 2% lidocaine with 1:200,000 adrenaline in pain control in extraction of mandibular posterior teeth: A double-blind study - Rishab Ranjan; S N Santhosh Kumar; Manju Singh (Wolters Kluwer Medknow Publications, 2018)
Background: Two percent lidocaine hydrochloride is the gold standard for dental anesthesia against which newer local anesthetic agents may be compared. 0.75% ropivacaine is a newer, long-acting amide local anesthetic agent with inherent vasoconstriction property. Aim: This study aims to compare the efficacy of 0.75% ropivacaine and 2% lidocaine hydrochloride with 1:200,000 adrenaline in pain control in extraction of mandibular posterior teeth. Settings and Design: This is a prospective, double-blind, and split-mouth study. Subjects and Methods: Twenty patients were divided into two groups according to the right and left sides of patient - side A and side B. The side, where 0.75% ropivacaine was to be administered, was randomly selected by flip coin method. Then, the pterygomandibular and long buccal nerve blocks were administered with 0.75% ropivacaine and necessary dental extraction was performed. After 1 week, the same procedure was repeated using 2% lidocaine hydrochloride with 1:200,000 adrenaline. The parameters assessed were pain on injection, onset of anesthesia, pain during the extraction, and duration of anesthesia. Statistical Analysis Used: The nonparametric data were assessed by Mann Whitney "U" test. Results: The mean onset of action for solution A was 7.15 ± 4.934 min and for solution B was 9.75±5.128 min. This was statistically significant. The mean duration of action, pain on injection, and pain during extraction were not significant. Conclusion: This study clearly states that there is no clear advantage of using 0.75% ropivacaine in pterygomandibular nerve block over the gold standard. However, more clinical studies with larger sample size are necessary.